1997
DOI: 10.1093/nar/25.21.4400
|View full text |Cite
|
Sign up to set email alerts
|

Position effects in mice carrying a lacZ transgene in cis with the  -globin LCR can be explained by a graded model

Abstract: We studied transgenic mice carrying the lacZ reporter gene linked to the erythroid-specific beta-globin promoter and beta-globin locus control region (LCR). Previously, we had demonstrated that the total level of expression of beta-galactosidase enzyme, which is the product of the lacZ gene, varies widely between different transgenic mice due to position effects at the sites of transgene integration. Here, using the X-gal based in situ assay for beta-galactosidase activity, we found that the percent erythroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…4A-C acting element that shields the transcriptional units from the surrounding DNA, exists in the full-length LCR but not in HS core elements. In fact, LCR containing HS4, 3, 2, 1 does not confer position-independent expression onto the b-globin promoter-driven lac Z gene in transgenic mice (Guy et al 1996;Guy et al 1997). HS5 59 to HS4 was shown to have the properties of an insulator (Li and Stamatoyannopoulos 1994).…”
Section: Discussionmentioning
confidence: 98%
“…4A-C acting element that shields the transcriptional units from the surrounding DNA, exists in the full-length LCR but not in HS core elements. In fact, LCR containing HS4, 3, 2, 1 does not confer position-independent expression onto the b-globin promoter-driven lac Z gene in transgenic mice (Guy et al 1996;Guy et al 1997). HS5 59 to HS4 was shown to have the properties of an insulator (Li and Stamatoyannopoulos 1994).…”
Section: Discussionmentioning
confidence: 98%
“…We considered the possibility that this pattern of expression might represent an artifact of the ␤-galactosidase reporter gene, since it has been reported that the ␤-galactosidase cassette interferes with the ability of the ␤-globin locus control region to confer position-independent expression (30), and it has been suggested that the ␤-galactosidase sequence may act as a nucleation point for the formation of heterochromatin in definitive erythroid cells (71). However, several groups have shown that a variety of erythroid enhancers, including the ␤-globin locus control region (30,31), the ␣-globin Ϫ40 element (56,70), and the EKLF Ϫ950 promoter (77), can direct expression of ␤-galactosidase to definitive erythroid cells in transgenic mice. Instead, we favor the alternative explanation that the 3.7-kb fragment containing the ϩ40 region exhibits intrinsic specificity for the primitive erythroid lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in adult mice, the β-galactosidase reporter gene may cause inactivation of the +19 core enhancer but not the larger +18/19 fragment. Inactivation of regulatory regions linked to lacZ transgenes has been reported previously and has generally been attributed to the prokaryotic origin of the lacZ sequence [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Failure of expression in adult SV/lac/19 transgenic mice would also be consistent with the suggestion that the +19 core enhancer may require additional sequences outside the core enhancer to maintain expression throughout ontogeny. Alternatively, the β-galactosidase reporter gene may not faithfully report enhancer activity in adult mice, a scenario that has been suggested previously [34][35][36][37][38][39]. To distinguish these possibilities, β-galactosidase was replaced by the mammalian reporter gene human PLAP.…”
Section: Scl +19 Core Enhancer Targets Plap Expression To Endotheliummentioning
confidence: 99%